Evidence for 2f$_{1/2}$ neutron strength in the low-energy structure of $^{144,146,148,150}Nd isotopes - Holden, J.; Benczer-Koller, N.; Jakob, G.; Kumbartzki, G.; Mertzimekis, T. J.; Speidel, K.-H.; Macchiavelli, A.; McMahan, M.; Phair, L.; Maier-Komor, P.; Stuchbery, A.E.; Rogers, W. F.; et al. (Phys. Lett. B, 2000)
The Bardeen model - the first regular black hole model in General Relativity - is reinterpreted as the gravitational field of a nonlinear magnetic monopole, i.e., as a magnetic solution to Einstein equations coupled to a nonlinear electrodynamics. (C) 2000 Elsevier Science B.V.
Keywords: article; electrochemical analysis; gravity; magnetic field; mathematical analysis; mathematical computing; mathematical model; nonlinear system